2001
DOI: 10.1002/1521-3757(20010504)113:9<1713::aid-ange17130>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Dodeca(benzyloxy)dodecaboran B12(OCH2Ph)12: ein stabileshypercloso-B12H12-Derivat

Abstract: Durch Per‐O‐benzylierung von [closo‐B12(OH)12]2− 12− mit Benzylchlorid und anschließende Oxidation mit zwei Äquivalenten FeIII gelang die Synthese von 2, dem Per(benzyloxy)‐Derivat von hypercloso‐B12H12 (siehe Schema). Verbindung 2 wurde 11B‐NMR‐ und elektronenspektroskopisch, massenspektrometrisch, cyclovoltammetrisch und röntgenographisch charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Various reports of electrochemical redox transformations between closo -dianionic and hypercloso -neutral boron subhalide clusters with n = 8−11 consistently show that the two electrons are transferred in separate one-electron steps at distinguishable redox (or formal) potentials E 0 . ,,,, The E 0 of the two steps are separated by several hundred mV, a result which is also found for the benzyloxy−B 12 cluster mentioned above . This “normal” potential ordering is usually an indication that no appreciable reorganization of the molecular structure is involved in the redox reactions …”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Various reports of electrochemical redox transformations between closo -dianionic and hypercloso -neutral boron subhalide clusters with n = 8−11 consistently show that the two electrons are transferred in separate one-electron steps at distinguishable redox (or formal) potentials E 0 . ,,,, The E 0 of the two steps are separated by several hundred mV, a result which is also found for the benzyloxy−B 12 cluster mentioned above . This “normal” potential ordering is usually an indication that no appreciable reorganization of the molecular structure is involved in the redox reactions …”
Section: Introductionmentioning
confidence: 60%
“…Although they are exceptions to Wade's rules, such hypercloso compounds have been isolated in the boron subhalide series, e.g., for X = Cl and n = 8 and 9. , Their stability is explained by a combination of the π-donor properties of the halogen atoms and steric effects . Similar stabilization was observed for B 12 (OCH 2 Ph) 12 …”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…12 These so-called camouflaged polyhedral borane derivatives 13 serve as cores for the synthesis of dendrimer-like derivatives known as closomers. 14 Very recently it has been demonstrated that the spherical sheath of hydroxyl groups in 4 can be fully derivatized affording closomeric dodecaesters 14,15 and dodecaethers, 16,17 respectively. Furthermore, dodecaborates bearing twelve organic linkers with terminal functionality were synthesized 18 for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%